Geometric imperfections of additive manufactured members. (1st February 2022) - Kraus, M.; Winkler, P.; Hammer, S.; Reimann, J.; Hildebrand, J.; Bergmann, J.P.
Highlights: Measuring of the manufacturing tolerances of Wire-Arc-Additive-Manufactured members with destruction free 3D-scanning methods like structured light scanning and computed tomography. Determination and statistical investigation of the geometrical imperfections like diameter, out of roundness, straightness, wall thickness and also pore distribution of additive manufactured circular hollow profiles. Classification of the measured imperfections compared to the standards of hot finished and cold formed hollow profiles. Comparison of the bearing capacity of Wire-Arc-Additive-Manufactured members derived in flexural buckling tests to conventional manufactured profiles. Abstract: Challenges in civil engineering and construction industries increase, and simultaneously it is necessary to provide a sustainable utilization of resources. Optimising material applications and manufacturing processes is therefore essential for modern constructions. Highly optimised structural components are already in use in lightweight constructions as well as in aircraft and vehicle industries. In the course of digitisation, new possibilities have evolved in recent years for producing individual and optimized solutions with regard to the consumption of materials, especially in construction industries. Methods of generative or additive manufacturing are employed to develop various prototypes of structural components. In this context, Wire-Arc-Additive-Manufacturing (WAAM) is a promising method for steel structures. However, it remains to be investigated to what extent dimensional accuracy, surface finish, weld quality and repeated thermal influences from the build-up process affect the structural behaviour of corresponding members. This paper deals with the geometric imperfections of corresponding additively manufactured profiles and exemplifies their influence on the bearing capacity.